'A Saxon who's learnt a lot from the Americans': Clemens Meyer in a Transnational Literary Context. (February 2018) - Matthes, Frauke
Abstract : In recent years, Clemens Meyer has emerged as the literary voice of societal underdogs. Initially celebrated as the 'tattoo-man of German literature' (Elmar Krekeler) whose 'rough' East German background seemed to have certified the authenticity of his subject, with his growing success, Meyer has managed to shake off the exclusive, and somewhat limiting, label of 'East German writer' with its often specifically provincial associations. The publication of his latest novel Im Stein (2013), which, translated as Bricks and Mortar (2016), was longlisted for the Man Booker International Prize in 2017, has finally led to Meyer's recognition as a more highbrow writer whose work has entered the transnational literary field. In his novel, Meyer self-consciously references world literary predecessors who have inspired him (for example Dos Passos and Hemingway) but adapts these literary models to develop a singular style that goes beyond mere intertextual allusions. My reading of Im Stein, a multi-voiced novel that revolves around organized prostitution in an unnamed East German city post-1989, thus ties in with recent debates focussing on the notion of 'world literature'. Following Gayatri Chakravorty Spivak's thoughts on 'singularity' in relation to world literature, I argue that it is precisely Meyer's engagement with the specificity of his subject matter through writing 'transnationally' that allows the author to achieve 'singularity'. This then paves the way for his work's 'universalizability' and, consequently, for Meyer's conscious adaptation of his work to world literature.